Influence of Sowing Depth and Shade on Emergence and Seedling Growth of Centrosema pubescens - Muhammad Rusdy; Rinaldi Sjahril (International Journal of Agriculture System, 2014)
Depth of sowing and shade levels were two ecological factors affecting early establishment of a plant. The effects of sowing depths of seeds and shade on seedling emergence, morphological traits and seedling biomass of Centrosema pubescens were examined. The seeds were sown at the depth of 2, 4, 6 and 8 cm and shaded at levels of 0 (full sunlight) and 50%. Analysis of variance showed a significant effect (P<0.05) of sowing depth on seedling performances. Sowing at the depth of 2 cm produced the highest percentage of seedling emergence, the shortest days to emergence, the biggest seedling diameter and thegreatest seedling biomass. Shade significantly (P<0.05) increased seedling height and shootroot dry weight ratio. The findings indicate that for improved growth and dry matter yield, Centrosema pubescens seeds should be sown at a depth of 2 cm.